THE SOCIAL SECURITY FOR AGING IN HONG KONG AND INDONESIA: HISTORICAL PERSPECTIVE - Riskianingrum, Devi (Jurnal Kajian Wilayah, 2019)
Entering the 1970s, Hong Kong became first cities that encountered the challenges of aging population. These were due to the steady increase of Hong Kong peopleâ€™s life expectancy, followed by declining the birth rate of Hong Kongâ€™s women. These have transformed Hong Kong into an aging society. To address the issues of aging society, The Hong Kong government initiated various policies, ranged from social security policies, active aging, and older people participation as efforts to maintain long term sustainability of their economic growth. As for Indonesian condition, the aging issues still considered less important compare to economy and politics issues. The purpose of this paper is to describe the social security issues in Hong Kong and Indonesia as an effort to get the big picture of aging management in both countries. Examining mainly on the issue of the regulation and its implementation with descriptive analysis approach, I revealed that the Hongkong government tends to focus on the practice of active aging, life learning program and neighborhood-based mutual help network program. In the meantime, the aging management in Indonesia is relatively still overlooked. Hence this paper aims for an input for Indonesian stakeholders in Aging Management.Keywords: aging society, social security, Hong Kong, IndonesiaAbstrakMemasuki tahun 1970-an, Hong Kong menjadi kota pertama yang menghadapi tantangan populasi yang menua (aging society). Hal ini terjadi karena pertumbuhan angka harapan hidup yang tinggi, serta diikuti dengan menurunnya jumlah kelahiran pada perempuan di Hong Kong. Hal ini perlahan tetapi pasti merubah wajah Hong Kong menjadi populasi yang menua (aging society). Untuk menangani isu ini, pemerintah Hong Kong menerbitkan berbagai peraturan, mulai dari kebijakan jaminan social bagi masyarakat lansia, lansia aktif, serta partisipasi lansia pada kegiatan ekonomi, sebagai usaha menjaga stabilitas pertumbuhan ekonomi negaranya. Tujuan penulisan ini adalah menjelaskan isu-isu jaminan social di Hongkong dan di Indonesia dalam upaya mendapatkan gambaran besar pengelolaan masyarakat menua di kedua negara. Berfokus pada permasalahan regulasi dan implementasi atas peraturan yang terbitkan, dengan menggunakan pendekatan deskriptif-analitis, dapat disimpulkan bahwa pemerintah Hong Kong lebih mengutamakan aplikasi program lansia-aktif (active aging), program pembelajaran kehidupan (life-learning program) dan program gotong royong komunitas. Sementara itu, pengelolaan masyarakat lansia di Indonesia masih belum menjadi prioritas. Oleh karena itu tulisan ini diharapkan menjadi masukan bagi para pemangku kepentingan yang terkait dalam pengelolaan lansia.Kata kunci: masyarakat menua, jaminan sosial, Hong Kong, IndonesiaÂ